PENGARUH MODEL PEMBELAJARAN MASTERY LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK MATA PELAJARAN AKIDAH AKHLAK DI MTs AN-NAHDLAH LAYANG MAKASSAR - Nurul Qadriyyah. Ak, Nurul; Akhmad Syahid; Subaedah; Hasibuddin Mahmud; Syarifa Raehana; Abdul Wahab (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to: (1) analyze the mastery learning model in the subject of faith and morals at MTs An-Nahdlah Layang Makassar. (2) evaluate student learning outcomes in the subject of faith and morals at MTs An-Nahdlah Layang Makassar. (3) identify the effect of the mastery learning model on student learning outcomes in the subject of faith and morals at MTs An-Nahdlah Layang Makassar. The method used is quantitative research. The population in this study was all students at MTs An-Nahdlah Layang Makassar, totaling 167. The sample used was 118 respondents using cluster proportional random sampling technique. Data collection technique was carried out by distributing questionnaires to respondents. The data analysis used was descriptive statistical analysis, inferential statistical analysis, simple linear regression analysis.The results of this study indicate that the influence of mastery learning on student learning outcomes in the subject of aqidah akhlak at MTs An-Nahdlah Layang Makassar partially is (1) The mastery learning variable obtained a significance value of < 0.05 (0.001 < 0.05) and tcount > ttable (4.455 > 1.981) with a percentage of 45%> 20% meaning that there is a significant influence of mastery learning on student learning outcomes in the subject of aqidah akhlak at MTs An-Nahdlah Layang. The simultaneous influence obtained by the coefficient of determination or R^2 is used to measure how far the model's ability to explain the independent variable (X), namely mastery learning and the dependent variable (Y), namely learning outcomes. The results of the calculation obtained a value of R^2 = 0.146 with a percentage of 14.6% of learning outcomes can be explained by the mastery learning variable. While the remaining 85.4% is influenced by other variables not examined in this study. Learning outcomes were categorized as moderate, with 67.8% of the 118 respondents.